The Performance Analysis for Embedded Systems using Statistics Methods - Wang Luyan; Shen Zhangguo; Chen Long (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Performance comparison for the computer system under different hardware platform & system structure is of vital importance in the study of the performance evaluation. The Performance Analysis for Embedded Systems by using statistics methods based on the randomized complete block designs was proposed. Using the randomized block design, the differences between conditions can be separated from the difference in the processing, and be separated from the experimental bias. A case study of automatic gate machines used in the automatic fare collection system of Shanghai Metro is presented. The obtained assessment results show that our approach is helpful and effective. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2864